Cultured Neural Networks: Optimization of Patterned Network Adhesiveness and Characterization of their Neural Activity. Issue 1 (8th July 2010) - Rutten, W. L. C.; Ruardij, T. G.; Marani, E.; Roelofsen, B. H.
Abstract : One type of future, improved neural interface is the "cultured probe". It is a hybrid type of neural information transducer or prosthesis, for stimulation and/or recording of neural activity. It would consist of a microelectrode array (MEA) on a planar substrate, each electrode being covered and surrounded by a local circularly confined network ("island") of cultured neurons. The main purpose of the local networks is that they act as biofriendly intermediates for collateral sprouts from the in vivo system, thus allowing for an effective and selective neuron–electrode interface. As a secondary purpose, one may envisage future information processing applications of these intermediary networks. In this paper, first, progress is shown on how substrates can be chemically modified to confine developing networks, cultured from dissociated rat cortex cells, to "islands" surrounding an electrode site. Additional coating of neurophobic, polyimide-coated substrate by triblock-copolymer coating enhances neurophilic-neurophobic adhesion contrast. Secondly, results are given on neuronal activity in patterned, unconnected and connected, circular "island" networks. For connected islands, the larger the island diameter (50, 100 or 150 μm), the more spontaneous activity is seen. Also, activity may show a very high degree of synchronization between two islands. For unconnected islands, activity may start at 22 days in vitro (DIV), which is two weeks later than in unpatterned networks.